Anya's ghost - Brosgol, Vera. (New York : First Second, 2011)
Anya, embarrassed by her family and lacking confidence in her body and her social skills, finally finds a friend after falling down a well, but quickly learns there are drawbacks to having a ghost for a friend.
Booklist starred
Bulletin of the Center for Children's Books starre
School Library Journal starred
Booklist starred, March 2011
Bulletin of the Center for Children's Books starre, June 2011
Kirkus Starred, May 2011
Keywords: High schools -- Comic books, strips, etc -- Juvenile fiction; Interpersonal relations -- Comic books, strips, etc -- Juvenile fiction; Russian Americans -- Comic books, strips, etc -- Juvenile fiction; Self-esteem -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Ghost stories; High schools -- Fiction; Interpersonal relations -- Fiction; Russian Americans -- Fiction; Self-esteem -- Fiction; Comic books, strips, etc; Ghost stories; Graphic novels; High schools -- Comic books, strips, etc -- Fiction; Interpersonal relations -- Comic books, strips, etc -- Fiction; Russian Americans -- Comic books, strips, etc -- Fiction; Self-esteem -- Comic books, strips, etc -- Fiction; Ghost stories; Graphic novels